Validation of an enzyme-linked immunoassay assay for osteocalcin, a marker of bone formation, in dried blood spots - Geeta N. Eick (2020)
© 2020 Wiley Periodicals, Inc. Objectives: Investigating factors that contribute to bone loss and accretion across populations in remote settings is challenging, particularly where diagnostic tools are scarce. To mitigate this challenge, we describe validation of a commercial ELISA assay to measure osteocalcin, a biomarker of bone formation, from dried blood spots (DBS). Methods: We validated the Osteocalcin Human SimpleStep ELISA kit from Abcam (ab1951214) using 158 matched plasma and DBS samples. Passing-Bablok regression analysis assessed the relationships between plasma and DBS osteocalcin concentrations. Dilutional linearity and spike and recovery experiments determined if the DBS matrix interfered with osteocalcin measurement, and intra- and inter-assay coefficients of variation (CVs) were calculated. Limit of detection, analyte stability, and specific forms of osteocalcin measured by the kit were also investigated. Results: Mean plasma osteocalcin value was 218.2 ng/mL (range 64.6-618.1 ng/mL). Linear relationships existed between plasma and DBS concentrations of osteocalcin, with no apparent bias in plasma vs DBS concentrations. There was no apparent interference of the DBS matrix with measurement of osteocalcin in DBS. Intra-assay CV for DBS was ~8%, while average inter-assay CV was 14.8%. Limit of detection was 0.34 ng/mL. Osteocalcin concentrations were stable in DBS stored at −28°C and room temperature, but not those stored at 37°C. This ELISA kit detects total osteocalcin. Conclusions: Osteocalcin, a bone formation biomarker, can be measured from DBS. Combined with a previously validated DBS assay for TRACP-5b, a bone resorption biomarker, these assays have the potential to help researchers disentangle the many factors contributing to bone strength.